The role of collagen and collagen I/III ratio in pathological conditions: insights into molecular mechanisms and therapeutic approaches - Kanniyappan, Hemalatha; Chathurika Rathnayake, Rathnayake A.; Osamor, Jude; Islam, Maria; Wang, Rong R. (Frontiers in Bioengineering and Biotechnology, 2025)
Collagen is the predominant structural protein, contributing to 25%–30% of total body protein. It is vital for maintaining the strength, flexibility, and structural integrity of connective tissues throughout the human body. Of the 28 identified collagen types, collagen I and collagen III are especially critical - collagen I imparts tensile strength, while collagen III enhances matrix flexibility. Disruptions in collagen structure and composition are frequently associated with aberrant collagen I and collagen III ratio that compromises tissue functions and contributes to pathological conditions affecting bone (osteoporosis), oral tissues (periodontal disease), wound healing (diabetic complications), reproductive organs (ovarian cancer), and pelvic support structures (pelvic organ prolapse), among others. These alterations arise from aging, genetic polymorphisms, and disease factors that disrupt collagen synthesis, assembly, and degradation. This review highlights recent advances in understanding the role of collagen and collagen I/III ratio in pathophysiological processes and deliberates emerging therapeutic interventions designed to restore collagen equilibrium, encompassing biomaterials, stem cell therapies, gene editing techniques, and biophysical stimulation modalities. Future directions in tissue-engineered extracellular matrix development, precision medicine applications, and combined therapeutic strategies are discussed as transformative approaches for managing collagen-associated disorders and improving patient outcomes.